Whey protein isolate edible films incorporated with essential oils: Antimicrobial activity and barrier properties - Çakmak, Hülya; Özselek, Yeşim; Turan, Osman Yağız; Fıratlıgil, Ebru; Karbancioğlu-Güler, Funda (Polymer degradation and stability, 2020)
Improvement of innovative biopolymers obtained from agricultural sources or food-waste products is one of the leading technologies to preserve quality, freshness and safety of food materials. The use of biopolymers in the packaging applications and their film forming ability reveal the idea of edible films which are also environment friendly. Starch, cellulose derivatives, chitosan/chitin, gums, and animal or plant-based proteins can be accepted as an option to obtain edible films for extending the shelf life of the foods. Film forming proteins provide mechanical stability and can be obtained from animals (casein, whey, gelatin, egg albumin) or plant sources (corn, wheat, rice). Flexibility of the protein network can be enhanced with plasticizers, additionally water permeability can be altered by the addition of oils or beeswax which are hydrophobic materials. Essential oils, in the concentration range of 0.05–0.1%, have demonstrated activity against pathogens. Whey protein isolate of 96% protein ratio (at 8% (w/v)), glycerol, lemon and bergamot essential oils were used for film preparation. Optimum concentrations of constituents of edible film were determined with response surface methodology as 39.2% for glycerol and 4.5% for essential oil. Essential oil concentration is higher than the value which was determined after MIC determination so this amount is effective against S. aureus and E. coli. •Whey protein isolate (at 8% (w/v)), glycerol, lemon and bergamot essential oils were used.•Essential oils, in the range of 0.05–0.1%, have demonstrated activity against pathogens.•Optimum concentrations were determined with RSM as 39.2% for glycerol and 4.5% for essential oil.•Films showed remarkable responses against water vapor and oxygen permeability.